A NEW SPECIES OF ADINANDRA (PENTAPHYLACACEAE) FROM INDIA - Pathak, M. K.; Bhaumik, M.; Krishna, G. (Edinburgh Journal of Botany, 2014)
A new species, Adinandra kamalae M.K.Pathak, Bhaumik & G.Krishna (Pentaphylacaceae), is described from Upper Siang District, Arunachal Pradesh, India.